Pencatatan Keuangan Digital Melalui Aplikasi Accurate dan Esensi Solusi Buana Core Pada Kantor My Kopi-O Lombok - Limas, Cindy Cornelia; Hendri, Wira; Wardhana, Helna (Insan Kreasi Media, 2024)
The transformation of the financial industry has not only impacted society but has also significantly influenced industry players in Indonesia. This transformation is evidenced by the availability of numerous digital financial applications that can be accessed either for a fee or free of charge, such as Accurate and ESB Core. The use of these applications is considered to enhance the effectiveness of corporate financial reporting. Therefore, this community service activity aims to assist My Kopi-O Lombok in implementing financial transaction recording through the Accurate and ESB Core applications. The methodology for this activity comprises three phases: preparation/planning, execution, and evaluation. Several activities conducted include recording financial transactions into the system, inventory management, initial branch data setup, and petty cash management. All activities were completed within one month. The results of this activity demonstrate an increase in the effectiveness of financial reporting for My Kopi-O Lombok, as digital recording has proven to facilitate the work of the finance department. It is hoped that through this activity, the company will continue to intensify its use of digital financial applications to maximize revenue and minimize operational expenses that can still be reduced by the company.